Våld utan blåmärken - En komparativ analys av den svenska lagstiftningen mot psykiskt våld i nära relation, i ljuset av Istanbulkonventionen - Svensson,Johanna (2025)
Psychological violence within the context of domestic abuse has long consti-tuted a pervasive issue. Although it represents the most prevalent form of vi-olence in intimate relationships, it is paradoxically the least frequently reported type of abuse. Both Sweden and the other Nordic countries are part of the Istanbul Convent-ion, which establishes standards for the criminalization of violence against women. In Sweden, multiple legislative initiatives have been undertaken over the years; most recently, in August 2022, when an explicit criminalization of psychological abuse as a distinct offense was proposed. This proposal has faced criticism from several consultative bodies, which contend that the current legislation is adequate and that efforts should instead focus on enhan-cing the effective implementation of existing provisions. This paper examines current Swedish legislation addressing psychological violence in intimate relationships, comparing it to Norwegian legislation, where a specific offense targeting psychological violence has been introduced. The analysis is conducted within the framework of the Istanbul Convention’s requirements and demonstrates that, while there are both similarities and diffe-rences between the countries’ legislative approaches and their alignment with the Convention, the similarities outweigh the differences. Of particular interest is the finding that the convergence between the national legislations is more pronounced than their divergence.
Keywords: Straffrätt